Analysis of Students' Enthusiasm for Learning in Preparing for State University Entrance Exams at SMAN 2 Batu - Agustin, Hani Nurzaina; Juliana, Jusniar Sri; Hotifah, Yuliati; Bintoro, Agus; Pratiwi, Awalya Siska (Universitas Negeri Malang, 2024)
Enthusiasm is an attitude of students characterized by great eagerness or interest, as well as active participation in learning. This study aims to understand the enthusiasm of students at SMAN 2 Batu in preparing for state university entrance exams. The selection process for university admission requires readiness to help students achieve their desired university. This study explores various factors contributing to student motivation and examines how these elements affect their academic performance and preparedness for exams. Using a combination of surveys and interviews, data was collected from a representative sample of students. The results indicate that personal ambition, family encouragement, and access to quality educational resources are key determinants of student enthusiasm. Furthermore, the study found that social interactions and participation in school activities significantly enhance students' commitment to their studies. This research concludes that fostering a supportive and resource-rich learning environment is crucial to maximizing student enthusiasm and success in entrance exams. These findings provide valuable insights for educators and administrators in developing strategies to support student engagement and achievement. Keywords: enthusiasm; motivation; academic achievement; high school students